Pengaruh growth opportunity, likuiditas, dan leverage terhadap nilai perusahaan dengan profitabilitas sebagai variabel intervening - Pratiwi, Adillah; Muthohar, Ahmad Mifdlol (Nur Science Institute, 2021)
The purpose of this study is to explain the effect of growth opportunity, liquidity, and leverage on firm value with profitability as an intervening variable (study at PT Bank Panin Dubai Syariah for the period 2016-2020). This research uses quantitative research by using path analysis. This study uses secondary data in the form of time series monthly financial data of Bank Panin Dubai Syariah from January 2016 to December 2020. This study indicates that the growth opportunity variable is insignificant to firm value, liquidity harms firm value, leverage harms firm value, and profitability harms firm value. In addition, the growth opportunity is not significant to profitability, liquidity harms profitability, and leverage harms profitability. After path analysis, profitability cannot mediate the effect of growth opportunity on firm value, profitability is not able to mediate the effect of liquidity on firm value, but profitability can mediate the effect of leverage on firm value.